Orang-utans’ (Pongo pygmaeus wurmbii) Activity Pattern in Camp Release and Feeding Site of Lamandau Wildlife Sanctuary, Central Borneo, Indonesia - Novita Amalia; Dyah Perwitasari-Farajallah; Sri Suci Utami-Atmoko; Azhari Purbatrapsila (Universitas Gadjah Mada, 2023)
The Bornean orang-utan (Pongo pygmaeus wurmbii) release process at Lamandau Wildlife Reserve applies the soft-release method. In this method, there is still provisioning additional food on the feeding site by human. The existence of camp release and feeding sites in the vicinity of release forests is assumed to have an impact on orang-utans’ activity patterns. This assumption is related to the principle of releasing them into their natural forest habitat, namely by reducing direct interaction between humans and orang-utans. The aims of this research were: (i) to measure the intensities of orang-utan presence on camp and feeding site, (ii) to analyze the correlation between phenology and orang-utan’s presence on camp and feeding site, and (iii) to assess orang-utan’s activity budgets, diet composition, and vertical used on camp, feeding site, and forest. Activity budgets of five group orang-utans with different categories based on age and sex were compared using the focal animal sampling method and instantaneous records. The analysis showed no correlation between the intensities of orang-utan presence and phenology. However, there were significant differences in activity patterns between adult and adolescent orang-utans. The findings revealed that adult orang-utans activity pattern tended to be high in resting at all observation locations while adolescents spending more their activity for feeding. Orang-utans at 0-10 m of height classes tend to do more activity. Almost all orang-utans feed on a non-forest diet (45-67%) in the camp release, feeding site, and surrounding. We assumed that the existence of a camp release and feeding site near the release point are affecting factors in a successful reintroduction of ex-rehabilitate orang-utans.